Definition of the Land Management Object: A Comprehensive Approach - E. A. Pozdnyakova (Теоретическая и прикладная юриспруденция)
In this article, a refined definition of the concept of “land management object” is proposed. The points of view of various scientists regarding the definition of the object of land management are analyzed. The basis for the study is the contradictory position of the legislator, which on the one hand speaks of the need to adopt a new law “On land management”, on the other hand borrows the term “object of land management” from the current law. Federal Law No. 78-FZ dated June 18, 2001 “On Land Management” has been repeatedly amended. Since the legal regulation of any institution cannot be effective without basic concepts, it is advisable to analyze the current definition of a land management object, rethink its content in relation to the demands of existing realities. The following methods were used in the study: historical, logical, analysis, generalization, study of literature and normative legal acts.